Suicide among Older Adults in Gunungkidul, Indonesia - Nurdiyanto, F A; Wulandari, Ririn Mamiek; Primasari, Ardi; Harjanti, Enggar Putri (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Older adults are vulnerable to suicidal crises due to decreased cognitive, health and psychosocial functions. Gunungkidul is a regency in Indonesia that has a demographic structure with an increasing older population and a high prevalence of suicide. This study aimed to determine the characteristics of suicide among older adults in Gunungkidul, Indonesia, from 2012 to 2022.Methods: This was a retrospective analytical descriptive study examining forensic reports of suicide from the Gunungkidul Resort Police, Indonesia, from 2012 to 2022. A total of 388 suicide reports were included, with 186 of them pertaining to older adult suicides. Demographic data and suicide methods were collected using descriptive statistics, and Chi-square analysis was performed to examine any associations or differences in the data.Results: Suicide cases in older adults were more dominant (55.03%) in all suicide cases in Gunungkidul. Hanging was the most prevalent method of suicide (96.2%) among older adults, and there was no difference in suicide methods between males and females (p=0.35). Furthermore, the older adults consisting of males (n=120) were more dominant than females (n=66), however, there was no significant difference across the age group in the youngest-old (60–69 years), the middle-old (70–79 years), and the oldest-old (≥80 years) age group (p>0.01).Conclusions: The prevalence of suicide in older adults in Gunungkidul exceeds other productive age groups, mostly males, and hanging is the most predominant method. Addressing suicide among older adults in Gunungkidul requires a holistic approach by considering individual and societal factors, which necessitates immediate attention to their health, psychological, and socio-economic needs through targeted interventions.